2015
DOI: 10.2119/molmed.2015.00013
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves Survival and Prolongs Life Following Hemorrhagic Shock

Abstract: Resveratrol has been shown to potentiate mitochondrial function and extend longevity; however, there is no evidence to support whether resveratrol can improve survival or prolong life following hemorrhagic shock. We sought to determine whether (a) resveratrol can improve survival following hemorrhage and resuscitation and (b) prolong life in the absence of resuscitation. Using a hemorrhagic injury (HI) model in the rat, we describe for the first time that the naturally occurring small molecule, resveratrol, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 47 publications
(47 reference statements)
2
34
2
Order By: Relevance
“…Sperry et al have shown that increase in IL-6 levels in HI correlates with multiple organ failure (MOF); male gender with higher IL-6 serum levels being more prone to MOF [14]. In our study in male SD rats, IL-6 level in plasma remained high at 2h and 3h post-resuscitation and was reduced with RSV administration consistent with the better outcome after injury [11]. This is consistent with a previous study that showed increased hepatic myeloperoxidase activity, cytokine-induced neutrophil chemoattractant (CINC)-1, CINC-3, ICAM-1, and IL-6 levels [6].…”
Section: Results and Discusionsupporting
confidence: 70%
See 3 more Smart Citations
“…Sperry et al have shown that increase in IL-6 levels in HI correlates with multiple organ failure (MOF); male gender with higher IL-6 serum levels being more prone to MOF [14]. In our study in male SD rats, IL-6 level in plasma remained high at 2h and 3h post-resuscitation and was reduced with RSV administration consistent with the better outcome after injury [11]. This is consistent with a previous study that showed increased hepatic myeloperoxidase activity, cytokine-induced neutrophil chemoattractant (CINC)-1, CINC-3, ICAM-1, and IL-6 levels [6].…”
Section: Results and Discusionsupporting
confidence: 70%
“…HI leads to declined organ function and mortality which are significantly improved by resuscitation in the presence of small molecule activators of SIRT1, resveratrol and SRT1720 [5, 11]. In order to understand the events leading to declined cardiac function, we tested the gene expression level of NF-κb, a transcription factor that promotes the expression of inflammatory genes and a panel of NF-κb-regulated cytokines in the heart following HI and resuscitation, by real time PCR (Figure 1).…”
Section: Results and Discusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies are necessary to determine whether additional targets exists for resveratrol and the contribution of SIRT1 activation in in vivo studies using resveratrol. A recent study published from our laboratory demonstrates that salutary effect of resveratrol in prolonging life after severe hemorrhage could be at least partially mimicked by the STAC SRT1720 (Ayub et al , 2015). …”
Section: Pharmacologic Therapiesmentioning
confidence: 97%